Resumes for dummies - Kennedy, Joyce Lain. (Hoboken, NJ : Wiley, 2011)
Get your career in gear and writer a winning resume to land that job interview. You'll learn the ropes and rules for a new era in recruiting and job searching and get expert tips on writing a resume that shines.
Previous ed.: Hoboken, NJ: Wiley, 2007.
Includes index.
Keywords: Resumes (Employment); Job hunting; Rum (Employment); Job hunting